Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/economies5020018
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom and Income Inequality: Does Political Regime Matter?

Abstract: There is a growing literature studying the effects of economic freedom and democracy on income inequality; nevertheless, the inequality-effects of both factors are apparently studied separately. This paper revisits the income inequality-economic freedom nexus and uncovers the role of political regime in explaining the relationship. Using the latest inequality data from Standardized World Income Inequality (SWIID) version 5.0 for a sample of countries up to 115 over 1970-2014 period, and via dynamic panel GMM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The political theory is known as a corporate citizenship group [26]. This group of theories focuses on the interactions and relationships between corporations and society, as well as the roles and positions of corporations and their responsibilities.…”
Section: Political Theorymentioning
confidence: 99%
“…The political theory is known as a corporate citizenship group [26]. This group of theories focuses on the interactions and relationships between corporations and society, as well as the roles and positions of corporations and their responsibilities.…”
Section: Political Theorymentioning
confidence: 99%
“…This is not surprising when considering the fact that within the EU context the size of government could be regarded as an indicator of welfare state characteristics. Ahmad (2017) examined the relationship between economic freedom and income inequality by taking into account the role of political regime. The data set used in this study covers 115 nations for the time span from 1970 to 2014.…”
Section: Related Literaturementioning
confidence: 99%
“…In a study covering 115 countries, Ahmad (2017) found that there is a positive relationship between the general economic freedom index and income inequality and that this relationship was stronger in terms of free foreign trade and market regulations (Ahmed, 2017: 23).…”
Section: Empirical Studiesmentioning
confidence: 99%